Análise da concentração plasmática de sTREM-1 e do perfil imunológico em pacientes com SARS-CoV-2 tratados com óxido nítrico inalado - Bitencourt, Douglas Antunes (2022)
The pandemic caused by SARS-CoV-2, also known as nCOVID-19, has been a worldwide concern since its beginning at the end of 2019. Infection with the new coronavirus is responsible for the development of Severe Acute Respiratory Syndrome, which, in addition to causing known clinical symptoms, it can lead to lung tissue impairment, exacerbation of the immune system and production of inflammatory cytokines, a condition called Cytokine Storm. There are approved treatments and vaccines and others are still being tested. The use of Inhaled Nitric Oxide is performed in certain pathologies and has been shown to be effective in in vitro studies due to its ability to inhibit viral replication when administered at certain concentrations. Elevated plasma concentrations of sTREM-1 in patients with COVID-19 are associated with disease severity. The TREM-1 pathway is involved in the inflammatory reaction and disease course of COVID-19 and therefore could be considered a therapeutic target in critically ill patients with COVID-19. However, whether the TREM-1 pathway has diagnostic or therapeutic value in COVID-19 remains to be seen. In this sense, the present study evaluated the plasma concentration of sTREM-1 and inflammatory cytokines before and after 5 days of the use of Inhaled Nitric Oxide in patients infected with COVID-19. Treatment with inhaled nitric oxide for five days did not significantly alter the concentrations of IL-1β, IL-6, IL-8, IL-10, IL-12p70, TNF-α, IFN-α and sTREM-1. However, plasma levels of sTREM-1 and IL-8 increased in patients over 55 years of age. During the period of 3, 5 and 7 days of ventilatory support, it resulted in a gradual increase in sTREM-1, IL-6, IL-8 and C-Reactive Protein.